2021
DOI: 10.1108/ccsm-08-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Cultural distance and customer orientation strategy of Chinese service MNEs under the belt and road initiative

Abstract: PurposeThe purpose of this paper is to explore mechanisms of cultural distance in the base of Chinese Service Multi-National Enterprise (MNE) settings. When attempting to enter overseas markets, many service MNEs face challenges caused by the cultural distance between the home and host countries. Culture distance attracts much attention in academia and industry. However, there are few empirical works to examine how cultural distance affects customer orientation strategies in a global supply chain. This paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…What's more, some related empirical studies concluded the discrepancy effects of the equally cultural distance on different countries, proving the existence of asymmetry [56][57][58][59]. Inconsistent conclusions appear in fields of export market selection [60][61][62], location choice of foreign direct investment (FDI) [15][16][17]63], entry mode choice of multinational enterprises [14,35,36,45,64,65], offshore governance choice [41], venture capital investment performance [66,67], acquisition performance [37,68,69], organizational performance [33,70,71], new product development performance [72]; H. [73,74], international expansion patterns [75,76], and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What's more, some related empirical studies concluded the discrepancy effects of the equally cultural distance on different countries, proving the existence of asymmetry [56][57][58][59]. Inconsistent conclusions appear in fields of export market selection [60][61][62], location choice of foreign direct investment (FDI) [15][16][17]63], entry mode choice of multinational enterprises [14,35,36,45,64,65], offshore governance choice [41], venture capital investment performance [66,67], acquisition performance [37,68,69], organizational performance [33,70,71], new product development performance [72]; H. [73,74], international expansion patterns [75,76], and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, the mainstream international management research still includes the composite cultural distance index proposed by Kogut and Singh (1988) to synthetically evaluate cultural distance (e.g. Ding et al, 2022;Lee et al, 2021;Li et al, 2021). Indeed, this index is one of the most popular measures based on Hofstede's country-level cultural dimension deviation (which is consistent with our choice of adopting Hofstede's theoretical framework).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 59%
“…Consumers from different cultural backgrounds will have different service expectations and product preferences. Thus, the firms' customer orientation strategy could be negatively affected by the cultural difference (Li et al, 2021), so be the salespeople's performance. Salespeople with high metacognitive CQ tend to have information acquisition skills and consciously understand the customers in different regions before and during interactions.…”
mentioning
confidence: 99%